Hormonal medication in medically assisted reproduction: a systematic review of assessments from patients. Issue 3 (March 2019) - Lankreijer, Kay; D'Hooghe, Thomas M; Apers, Silke; Sermeus, Walter; Repping, Sjoerd; Dancet, Eline AF
Abstract: Several hormonal fertility medications have comparable effectiveness. A literature review was conducted into patients' assessments regarding seven medication characteristics including 'side effects' and 'ease of use'. Medline, CINAHL and PsycINFO were searched for female fertility patients' written assessments of a hormonal medication. The tools used were appraised and common (i.e. ≥10%) unpleasant consequences were distinguished from rare ones. The 35 eligible studies did not rely on valid and reliable tools and did not provide patient assessments regarding all seven medication characteristics for any of the globally used medications. Evidence on medications for oocyte triggering was absent and for induction of pituitary quiescence it was scarce. Regarding medications for ovarian stimulation and luteal support, evidence on general side effects (mostly headache), local side effects (mostly pain), 'interference with home life' and 'impact on psychological wellbeing' was found. Evidence on 'ease of use' and 'required education' was only identified for medication for ovarian stimulation. Evidence on 'interference with work life' and 'compliance worry' was absent. This review calls for randomized controlled trials questioning patients with valid and reliable tools. In the meantime, this review's summary of the best available evidence can be integrated in decision aids facilitating personalized and informed medication choices.